Study of Ruthenium-Contamination Effect on Oxygen Reduction Activity of Platinum-Based PEMFC and DMFC Cathode Catalyst. Issue 1 (27th January 2022) - Kaplan, D.; Tereshchuk, P.; Olewsky, C.; Keinan, L.; Ben-Yehuda, O.; Shviro, M.; Natan, A.; Peled, E.
Abstract : We outline a systematic experimental and theoretical study on the influence of ruthenium contamination on the oxygen reduction activity (ORR) of a Pt/C catalyst at potentials relevant to a polymer electrolyte fuel cell cathode. A commercial Pt/C catalyst was contaminated by different amounts of ruthenium, equivalent to 0.15–4 monolayers. The resulting ruthenium-contaminated Pt/C powders were characterized by energy–dispersive x–ray spectroscopy (EDS), x–ray photoelectron spectroscopy (XPS) and scanning transmission electron microscopy (STEM) to verify ruthenium contamination. A rotating disk electrode (RDE) technique was used to study the influence of ruthenium on oxygen reduction kinetics. Density functional theory (DFT) calculations were performed to estimate the oxygen reduction activity of the platinum surface with increasing ruthenium coverage, simulating ruthenium-contaminated Pt/C. The binding energies of O and OH on the surfaces were used for activity estimations. It was found that the specific activity of the ORR at 0.85 V vs RHE exhibited an exponential-like decay with increased ruthenium contamination, decreasing by ∼45% already at 0.15 monolayer-equivalent contamination. The results of the DFT calculations were qualitatively in line with experimental findings, verifying the ability of the chosen approach to predict the effect of ruthenium contamination on ORR on platinum.